ADOPSI VARIETAS UNGGUL BARU PADI DI LAHAN RAWA - A. Ruskandar; Widyantoro Widyantoro; Septian Deni W; A. Rifki; I.A. Rumanti; I. Hasmi (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2019)
This research was conducted using a survey method carried out in two districts in the South Sumatra region namely Ogan Ilir and Banyuasin starting in March 2019. Ogan Ilir Regency represents the lebak swamp area while Banyuasin represents the Pasangsurut swamp area. The selection of provinces is determined by purposive sampling, which is chosen provinces that have a fairly large swampy land. Data collected includes: (1) Characteristics of respondents (age, sex, education, land area / arable land, (2) Reasons for choosing a vub to plant, (3) source of seeds and seed classes planted, and (4) data and information other relevant to the purpose of the study.This study aims to identify the level of adoption and development of new superior varieties (VUB) of rice in swamps and identify the reasons for farmers in adopting and planting VUBs.From the results of the study revealed that Ciherang is a common variety planted by respondents in Ogan Ilir, while IR 42 is a variety commonly planted in Banyuasin, transplanting planting is done twice by seedlings, generally done by respondents in Ogan Ilir, while seed planting is directly carried out by respondents in Banyuasin, most respondents in Ogan Ilir are not familiar with Inpara varieties, varieties planted in the two districts are generally not labeled.Some of the reasons cited by farmers grow varieties between high production, short service life, and pest resistance data Distribution of varieties in South Sumatra shows that Ciherang is still the dominant variety, while Inpara has not been recorded in the data held by local agencies.